Underwater undulatory swimming propulsion mechanism of left lower limb deficient swimmer using piv method - Nakazono, Y.; Shimojo, H.; Takagi, H.; Sengoku, Y.; Tsunokawa, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Para swimming has been adopted since the first Paralympic Games in 1960 and is one of the most popular sports for people with disabilities. Para swimmers are expected to maximize their own physical abilities and perform at their best, despite the disadvantages they may have compared to able-bodied swimmers due to their physical handicaps such as paralysis and defects. The World Para Swimming rules allow for underwater propulsion in the 15 m section from the wall after the start and after the turn, just as in swimming competitions. In this section, most swimmers use a propulsion technique called Underwater Undulatory Swimming (UUS). This UUS is similar to the propulsion technique of cetaceans, it keeps a streamlined position and propels itself through the water by moving its lower limb up and down. A previous study has shown that the swimming velocity of the underwater movement has the greatest impact on the starting phase (Burkett et al., 2010), indicating the importance of increasing the swimming velocity of the UUS. To increase the velocity of UUS, it is necessary to clarify the propulsive mechanism. Previous studies have attempted to elucidate the propulsive mechanism by visualizing the flow around the swimmer using the particle image velocimetry (PIV) method (Hochstein and Blickhan, 2011; Shimojo et al., 2019). Previous studies on UUS in able-bodied swimmers using the PIV method reported that it is propelled by vortex pairs generated by the motion of both feet (Shimojo et al., 2019). Three-dimensional joint movements such as hip internal/external rotation and ankle internal/external rotation have also been observed (Matsuda et al., 2021), and these joint movements are thought to be essential for the vortex pair collision and release generated by both feet. So how does a one-leg deficient swimmer, who performs UUS movements with only one leg, generate propulsive force? Like normal swimmers, the one-leg deficient swimmer is propelled by moving the lower limb up and down while maintaining a sreamlined position with both upper limbs elevated. However, it is unclear what kind of vortex is generated and momentum is obtained during these propulsions. Therefore, the purpose of this study is to clarify the mechanism of UUS propulsion in swimmers with a deficient lower limb on one sid